In vivo and ex vivo 19‐fluorine magnetic resonance imaging and spectroscopy of beta‐cells and pancreatic islets using GLUT‐2 specific contrast agents. (14th September 2016) - Liang, Sayuan; Louchami, Karim; Kolster, Hauke; Jacobsen, Anna; Zhang, Ying; Thimm, Julian; Sener, Abdullah; Thiem, Joachim; Malaisse, Willy; Dresselaers, Tom; Himmelreich, Uwe
Abstract : The assessment of the β‐cell mass in experimental models of diabetes and ultimately in patients is a hallmark to understand the relationship between reduced β‐cell mass/function and the onset of diabetes. It has been shown before that the GLUT‐2 transporter is highly expressed in both β‐cells and hepatocytes and that D‐mannoheptulose (DMH) has high uptake specificity for the GLUT‐2 transporter. As 19‐fluorine MRI has emerged as a new alternative method for MRI cell tracking because it provides potential non‐invasive localization and quantification of labeled cells, the purpose of this project is to validate β‐cell and pancreatic islet imaging by using fluorinated, GLUT‐2 targeting mannoheptulose derivatives ( 19 FMH) both in vivo and ex vivo . In this study, we confirmed that, similar to DMH, 19 FMHs inhibit insulin secretion and increase the blood glucose level in mice temporarily (approximately two hours). We were able to assess the distribution of 19 FMHs in vivo with a temporal resolution of about 20 minutes, which showed a quick removal of 19 FMH from the circulation (within two hours). Ex vivo MR spectroscopy confirmed a preferential uptake of 19 FMH in tissue with high expression of the GLUT‐2 transporter, such as liver, endocrine pancreas and kidney. No indication of further metabolism was found. In summary, 19 FMHs are potentially suitable for visualizing and tracking of GLUT‐2 expressed cells. However, current bottlenecks of this technique related to the quick clearance of the compound and relative low sensitivity of 19 F MRI need to be overcome. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Ex vivo 19 F MR spectroscopy confirms preferential uptake of 19 F fluoro‐deoxy‐mannoheptuloses in tissue with high expression of the GLUT‐2 transporter, such as liver, endocrine pancreas and kidney. However, in vivo 19 F MRI was not sensitive enough for non‐invasive detection within reasonable scan time.